Теоретико-игровые подходы к исследованию экономических ситуаций - Kulikova, Valentina; Kulbakov, Nikolay; Abdullin, Denis; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2016)
The objective of that Bachelor`s Thesis is learning of certain methods of Game Theory which are useful as daily problems of people as process's in business conditions. The object of that Bachelor`s Thesis is a problem with production of public goods and the subject of the paperwork is a theoretical foundation of sections of Game Theory - statistic games of complete or incomplete information dynamic games of complete or incomplete information. The Bachelor`s Thesis was divided into three parts: Theoretical part, Practical part 1 (setting problems) and Practical part 2 (modeling the problems).
Vedoucí práce: Nikolay Kulbakov
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: ekonomika predprijatija i menedžment [obor bakal. práce]; bakalářské práce; bachelor's theses